PENGEMBANGAN MODEL SIMULASI SISTEM DINAMIK UNTUK MENINGKATKAN EFISIENSI SISTEM OPERASIONAL TRANSPORTASI - Amaliah Faradibah; Erma Suryani (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2019)
If transport continues to increase, plus manufacturers competing to produce interesting transportation on the market, thus allowing the improvement of the transport users. If the increase occurs, it will cause congestion. Congestion was a factor that greatly affect the efficiency of the transport system, where the transportation system is a form of attachment and the interconnected between the passenger, shuttles and infrastructure that interact in order to transfer people or goods, which is covered in an order, either by natural or artificial or engineered. It takes the right planning strategies in addressing conditions congestion such as implementation of reconfiguration of the route network, a program that using dynamical systems in proper design and planning, and the determination of the most appropriate scenario can improve the efficiency of the transportation system. This research uses scenario through reconfiguration of network routes to improve the efficiency of the transportation system. in this study, this scenario is considered to be the most appropriate to increase the efficiency of vehicle travel time by way of the transfer of light vehicle routes that will go towards the Urip Sumoharjo street because it results in a reduction in travel time by 1.2% of travel time before the scenario.